2008
DOI: 10.1063/1.3055607
|View full text |Cite
|
Sign up to set email alerts
|

Elastic, dielectric, and piezoelectric properties of BaTeMo2O9 single crystal

Abstract: Ba Te Mo 2 O 9 is a noncentrosymmetric single crystal for nonlinear optical applications. In this letter, we report complete set of elastic, dielectric, and piezoelectric constants of BaTeMo2O9 single crystal determined by resonance technique and impedance analysis, the relative constants have been obtained and discussed. Our results show that BaTeMo2O9 crystal has excellent piezoelectric property (d34=30.25pC∕N, s44=36.46pm2∕N) and could be a promising candidate for piezoelectric applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…Over the last decade, Tao and Halasyamani groups et al have investigated the bulk crystal growths and characterizations of β-BaTeMo 2 O 9 [17], BaTeW 2 O 9 [18], Na 2 TeW 2 O 9 [19] and Cs 2 TeMo 3 O 12 [20]. These crystals exhibit excellent multifunctional properties, including piezoelectricity, pyroelectricity, electro-optic and NLO properties [21][22][23]. Cs 2 TeW 3 O 12 (P6 3 ) reported by Halasyamani group in 2003 displays a two-dimensional layered structure composed of [TeW 3 O 12 ] 2 À anionic layers with Cs þ cations located at voids between the layers for charge balance [14,24].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, Tao and Halasyamani groups et al have investigated the bulk crystal growths and characterizations of β-BaTeMo 2 O 9 [17], BaTeW 2 O 9 [18], Na 2 TeW 2 O 9 [19] and Cs 2 TeMo 3 O 12 [20]. These crystals exhibit excellent multifunctional properties, including piezoelectricity, pyroelectricity, electro-optic and NLO properties [21][22][23]. Cs 2 TeW 3 O 12 (P6 3 ) reported by Halasyamani group in 2003 displays a two-dimensional layered structure composed of [TeW 3 O 12 ] 2 À anionic layers with Cs þ cations located at voids between the layers for charge balance [14,24].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, single crystal BaTeMo 2 O 9 (space group P2 1 , a = 5.5346Å, b = 7.4562, c = 8.8342Å,ˇ= 90.897 • , Z = 2) was synthesized from a TeO 2 -MoO 3 system by the flux method by Tao et al [10]. As a multifunctional NCS compound, the refractive index, electro-optic tensor, dielectric and piezoelectric properties of single crystal BaTeMo 2 O 9 were also measured by them [10][11][12]. Their experimental data revealed that BaTeMo 2 O 9 is not only a potential nonlinear optical crystal but also a promising piezoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with BaMoO 4 crystal, BTM exhibits lower symmetry and possess more vibrational modes as additional Te-O 4 terahedron are incorporated to the crystal structure. 11,16 As shown in Fig. 1, there are much more Raman shifts in BTM spontaneous Raman spectrum than in BaMO 4 , whereas the three Raman shifts at 865.9-921.3 cm À1 are very similar to that of BaMoO 4 .…”
mentioning
confidence: 64%